Pengalaman Kepala Ruangan dalam Mengelola Ruang Rawat Inap pada Masa Pandemi Covid-19 - Yoga, Sukma Wisnu; Suyasa, I Gede Putu Darma; Rismawan, Made; Agustini, Ni Komang Tri (Jurnal Kesehatan, 2023)
Nurses are a milestone in achieving quality and professional health services. Since Covid-19 was declared a global pandemic, the Mangusada Hospital formed a special care unit, the Covid-19 Isolation Room. Hospitals, through line managers, are required to be able to prepare service management to comply with national health protocol standards while still prioritizing health and safety in the prevention and control of Covid-19 transmission. The purpose of this study was to describe the experience of the head of the room in managing inpatient rooms during the Covid-19 pandemic at the Mangusada Hospital in 2021. This research used a qualitative and phenomenological approach with data collection methods using in-depth interview techniques on March 1- April 30, 2021, at the Mangusada Hospital. Determination of the sampling technique using purposive sampling with a sample of 7 main participants and six triangulation participants. Data analysis in this study was carried out using the method of Colaizzi. The study resulted in 5 themes, namely, 1) changes in the function and management of the room, 2) anxiety, 3) adequate support, 4) limited facilities and infrastructure, and 5) hope that the pandemic will end soon. Based on the research results, the head of the room needs to understand and carry out management functions to support service in the inpatient room, which is his responsibility and expected to improve planning and human resources in the ward during the Covid-19 pandemic.